The Influence of Organizational Culture, Quality of Work Life, and Corporate Social Responsibility on Employee Performance at Santi Mebel Godean - Amelia, Ria Shinta; Ariani, Dorothea (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
An organization is said to be successful in achieving its goals. It really depends on the members of the organization. The success of an organization is not only determined by good business strategy, but also depends greatly on the quality and management of its members and analyzing the influence of organizational culture, quality of work life, and corporate social responsibility on the performance of Santi Mebel Godean employees. This research uses quantitative methods, data is obtained through questionnaires distributed to company employees. This research population involves all employees, with samples taken randomly. Regression analysis is used to test variable relationships, while descriptive statistical analysis provides an overview of the respondents. The results of this research are expected to be able to understand the factors that influence performance in the Santi Mabel Godean company environment. These results can be a basis for the company's organizational culture, quality of life in the workplace and corporate social responsibility to support optimal employee performance. The theoretical implications of this research can enrich human resource management, while the practice helps companies improve human resource management policies and practices.